Seasonal acoustic occurrence, diel‐vocalizing patterns and bioduck call‐type composition of Antarctic minke whales off the west coast of South Africa and the Maud Rise, Antarctica. Issue 2 (30th January 2020) - Shabangu, Fannie W.; Findlay, Ken; Stafford, Kathleen M.
Abstract: Seasonal occurrence, diel‐vocalizing patterns, and call‐types of Antarctic minke whales are described using bio‐acoustic recordings from the west coast of South Africa and the Maud Rise, Antarctica. In Antarctica, minke whale bioduck calls were detected in seven of nine months of hydrophone deployment (peaking in May and September) while downsweeps were only detected in June. Bioduck calls were sporadically detected in South African waters with peak calling in September/October, and no bioducks were detected from March through August. Bioduck call occurrence was high during daytime in Antarctica but there was no diel‐vocalizing pattern in South African waters. We split bioduck B call‐type into two subtypes: B1 with 13 ± 1 pulses (Dominello & Širović, 2016) and B2 with 9 ± 1 pulses (this study). Bioduck B2 was detected both in Antarctic and South African waters, with harmonics up to 2 kHz. Similar bioduck call‐types were detected in Antarctic and South African waters, with bioduck A2 being the most common. Month of the year was the most important predictor of bioduck occurrence both in Antarctic and South African waters. This is the first study to describe the seasonal occurrence, diel‐vocalizing behavior and call‐types of Antarctic minke whales off the South African west coast and eastern Weddell Sea.